A Discussion of “Audit Review: Managers' Interpersonal Expectations and Conduct of the Review” - Peecher, Mark E. (Contemporary Accounting Research, 2002)
Abstract Gibbins and Trotman's study both explores reviewer attributes that auditors judge to influence review quality and replicates earlier, largely experimental findings about preparer and reviewer decision behavior. Such exploration and intra‐method replication create opportunities to refine theory and better design future experimental and nonexperimental studies. Naturally, as with any study, the opportunities that this study creates are not without bounds. To help in thinking about these bounded opportunities, this discussion raises four topics that I have entitled “retro‐spective biases”, “stylization perceptions”, “manager styles”, and “real‐time review complexities”. After discussing these topics in turn, I end with a short summary.